A Pragmatic Analysis of Politeness Strategies in “Tenggelamnya Kapal Van der Wijck” - Ricky, Ricky; Afriana, Afriana (LPPM Universitas Putera Batam, 2024)
Politeness is to convey an expression as pleasantly as possible, which is necessary to reduce conflict with others. As a result, being polite is essential because it allows people to express themselves without offending others. The aim of this study is to examine the strategies of politeness utilized in the movie